Towards an automated framework to instantiate virtual networks in OpenFlow-based infrastructures. (2016) - Doriguzzi-Corin, Roberto; Salvadori, Elio; Gerola, Matteo
The explosion of cloud applications and data-centres technologies has recently renewed the interest of both academic and industrial research community on network virtualisation techniques. The increasing availability of programmable network devices and the pervasive adoption of a software-defined networking approach in all segments of the network are paving the way toward novel virtualisation approaches which aim at improving network management operations while guaranteeing a better utilisation of resources especially when compared to traditional overlay-based techniques widely used in data-centre settings. In this paper, the experience gained by the authors in the development and deployment of an innovative network virtualisation framework on an OpenFlow-based programmable experimental facility is provided and discussed in detail. Despite its specific application to a Future Internet testbed scenario, the proposed architecture is a first step toward a completely automatic management of virtual networks in OpenFlow-based software-defined networks.